3D Platinum–Lead Nanowire Networks as Highly Efficient Ethylene Glycol Oxidation Electrocatalysts. Issue 33 (14th July 2016) - Feng, Yonggang; Bu, Lingzheng; Guo, Shaojun; Guo, Jun; Huang, Xiaoqing
Abstract : A large‐scalable wet‐chemical approach to create networked Pt‐Pb nanowires (NWs) with tunable compositions is reported. Due to their 3D networked structure, alloy effect, rich defects/steps, and antipoisoning property of Pb, the networked Pt‐Pb NWs exhibit the best activity and durability towards ethylene glycol oxidation reaction (EGOR), compared with the networked Pt NWs and Pt/C.